The Microarray Gene Profiling Analysis of Glioblastoma Cancer Cells Reveals Genes Affected by FAK Inhibitor Y15 and Combination of Y15 and Temozolomide - Huang, Grace; Ho, Baotran; Conroy, Jeffrey; Liu, Song; Qiang, Hu; Golubovskaya, Vita (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Focal adhesion is known to be highly expressed and activated in glioma cells. Recently, we demonstrated that FAK autophosphorylation inhibitor, Y15 significantly decreased tumor growth of DBTRG and U87 cells, especially in combination with temozolomide. In the present report, we performed gene expression analysis in these cells to reveal genes affected by Y15, temozolomide and combination of Y15 and temozolomide. We tested the effect of Y15 on gene expression by Illumina Human HT12v4 microarray assay and detected 8087 and 6555 genes, which were significantly either up- or down-regulated by Y15-treatment in DBTRG and U87 cells, respectively (p<0.05). Moreover, DBTRG and U87 cells treated with Y15 changed expression of 1332 and 462 genes more than 1.5 fold, p<0.05, respectively and had 237 common genes affected by Y15. The common genes up-regulated by Y15 included GADD45A, HSPA6 (heat-shock 70); DUSP1, DUSP 5 (dual-phosphatase 5); CDKN1A (p21) and common down-regulated genes included kinesins, such as KIF11, 14, 20A, 20B; topoisomerase II, TOP2A; cyclin F; cell cycle protein: BUB1; PARP1, POLA1. In addition, we detected genes affected by temozolomide and by combination of Y15 and temozolomide treatment in U87 cells. Among genes up-regulated by Y15 and temozolomide more significantly than by each agent alone were: COX7B; interferon, gamma-inducible transcript: IFI16; DDIT4; GADD45G and down-regulated: KIF3A, AKT1; ABL; JAK1, GLI3 and ALDH1A3. Thus, microarray gene expression analysis can be effective in establishing genes affected in response to FAK inhibitor alone and in response to combination of Y15 with temozolomide that is important for glioblastoma therapy.
Keywords: brain